“REDISCOVERY” OF KNOWLEDGE ABOUT THE FUTURE: PERSPECTIVES OF RUSSIA’S SECURITY UP TO 2050 - S. A. Kravchenko; A. I. Podberezkin (Vestnik MGIMO-Universiteta, 2017)
The article deals with the dynamics of knowledge about the future, factors that determine the need for its »rediscovery« today, among which: the transition of mankind to the dominance of non-linear development; the destruction by globalization of the natural boundaries of civilizational formations, which led to direct interaction of local human civilizations and new conflicts between them; the formation of a unified socio-techno-natural reality; the emergence of complex systems potentially predisposed to the production of catastrophes disasters. This forced scientists to form new models of the future and, accordingly, to develop other theoretical and methodological tools of social forecasting on the basis of which scenarios of the medium-term (up to 2025) and long-term (up to 2050) visions of the international and military political situation are proposed. The authors proceed from the assumption that the validity of these scenarios and the confidence in the knowledge of security should emerge from a comprehensive account of the main stable and variable factors that determine and form the scenarios of Russia’s development in these periods. The most suitable method for long-term forecasting is the longitudinal-scenario method which is based on the creation of a model of a probable scenario of the international and military political situation. In order to accomplish this goal, the model needs a large empirical array of information that is analyzed in several stages by taking into account the influence of the main objective groups of factors that ultimately makes it possible to single out and justify three strategic directions of ensuring Russia’s security in the twenty-first century. The article comes to conclusion that future scenarios of Russia’s development depend on subjective factors such as the quality and intentions of the ruling political elite.